TINGKAT KESEJAHTERAAN PETANI KELAPA SAWIT DI KAMPUNG KERINCI KANAN KECAMATAN KERINCI KANAN - Dewi Sulistianingsih; Achmad Hidir (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2022)
Oil palm plantations are currently being considered as an alternative to changing the community's economy. Oil palm plantations have a significant impact on increasing income, particularly for farmers. As a result of this situation, almost all farmers have converted their land into oil palm plantations. The purpose of this research is to look into the walfare level of oil palm farmers in Kerinci Kanan Village, Kerinci Kanan sub-district, Siak Regency. To learn about the walfare level of oil palm farmers in Kerinci Kanan village, Kerinci Kanan sub-district, and what alternative strategies they use to deal with the sometimes unstable price of palm oil. The descriptive quantitative research methods are used in this study. The people in this study are oil palm farmers with 2 hectares of oil palm plantations. The census sampling technique was used, with the sample consisting of all oil palm farmers with a plantation area of 2 hectares. In this study, the sample size was 77 people. The researcher used observation, questionnaires, and documentation techniques to collect data. From the results of the research on 77 respondents, most of them have a low level of welfare.This can be seen in the income generated by their oil palm plantations, which remains low, being less than the minimum wage in Siak Regency. The selling price of oil palm fruit has a significant impact on respondents' income from their oil palm plantations. When the selling price of oil palm fruit falls, the income generated by oil palm farmers falls; conversely, when the selling price of oil palm fruit rises, the respondent's income from his oil palm plantation rises as well. As a result, oil palm farmers need to carry out a strategy to survive. Keywords: Welfare, Oil Palm Farmers